PENGARUH MEKANISME CORPORATE GOVERNANCE PADA MANAJEMEN LABA - Sari, A.A Intan Puspita; Dwija Putri, I G.A.M. Asri (E-Jurnal Akuntansi; Vol 8 No 1 (2014), 2014)
Implementation of Good Corporate Governance ( GCG ) has become a necessity for any company to achieve harmony between the interests of managers and stakeholders in achieving the main objectives of the company. GCG plays an important role as a mechanism for oversight of all operational activities of the company, so the application of good corporate governance is expected to reduce earnings management behavior that is opportunistic. Empirically testing purpose of this study was to examine the effect of corporate governance mechanisms consisting of kempemilikan managerial, institutional ownership, the proportion of independent board, board size and audit committee on earnings management. This study used the Modified Jones model to calculate discretionary accruals becomes a proxy of earnings management. The sample in this study is a manufacturing company that is listed on the Indonesia Stock Exchange. Sampling was done by purposive sampling method. Multiple linear regression analysis was used as an analytical technique in this study. Based on the discussion of the results of the study prove that managerial ownership, the proportion of independent board and audit committee negatively affect earnings management. However, two other corporate governance mechanisms, namely institutional ownership and board size no proven effect on earnings management.
Keywords: Earnings management, Corporate Governance